Pelatihan Pemasaran Online melalui Foto Produk dan Copywriting di Desa Tomplakan Tuntang Kabupaten Semarang - Tri Imaliya; Adi Suryo Ramadhan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Online marketing training for the community of Tomplakan Village, Tuntang Subdistrict, Semarang Regency in the hope of increasing competence, knowledge in online marketing can foster the entrepreneurial spirit of the Tomplakan Tuntang Village community. The participants were very enthusiastic and interactive in practicing product photos, how to market products to social media using copywriting techniques. The activity was conducted offline at the multipurpose building of Tomplakan Village Hall, Tuntang Sub-district, Semarang Regency. The targets in this training consisted of PKK elements, community leaders, ginger farmers and teenagers totaling 40 people. It is hoped that from the training practices and assistance of community service activities that the community will have the ability in the field of online marketing according to current technological developments.